Guided literacy instruction: Helping students read multimodal English-medium texts - Tungka, Novalita Fransisca (Indonesian Journal of Applied Linguistics, 2018)
This article reports a phenomenological study investigating the implementation of guided literacy instruction, geared to L2 students in reading multiple texts as the fabric of today’s literacy practice. Guided literacy instruction in this study aimed to promote the role of a student reader as a designer, navigator, interrogator, and interpreter in reading multimodal English-medium texts. Interviews, observations, and think-aloud protocols were used to collect data. Two L2 students volunteered to take part in this multimodal text-based reading project. Findings showed that the students experienced different reading activities resulting from the absence and presence of guided literacy instruction. The students’ experiences differed in the ways the students maximized the use of webpage text features, navigated texts across hyperlinks, and interpreted multiple modes of texts during a meaning making process. The empirical implication of this study is that future research is needed to investigate factors influencing the implementation of guided literacy instruction in reading multimodal English-medium texts. Pedagogically, multimodal text can be a meaningful learning resource that students can use to learn a range of knowledge and language resources beyond the classroom zone.